Development and psychometric properties the Barriers to Access to Care Evaluation scale (BACE) related to people with mental ill health - Clement, Sarah (BioMed Central, 2012)
BACKGROUND: Many people with mental illness do not seek or delay seeking care. This study aimed to develop, and provide an initial validation of, a comprehensive measure for assessing barriers to access to mental health care including a ‘treatment stigma’ subscale, and to present preliminary evidence about the prevalence of barriers experienced by adults currently or recently using secondary mental health services in the UK. METHODS: The Barriers to Access to Care Evaluation scale (BACE) was developed from items in existing scales, systematic item reduction, and feedback from an expert group. It was completed in an online survey by 117 individuals aged 18 and over who had received care from secondary mental health services in the past 12 months. Internal consistency, test-retest reliability, convergent validity (correlation of treatment stigma subscale with the Stigma Scale for Receiving Psychological Help (SSRPH) and with the Internalised Stigma of Mental Illness Scale (ISMI)), respondent opinion and readability were assessed. RESULTS: The BACE items were found to have acceptable test-retest reliability as all but one of the items exceeded the criterion for moderate agreement. The treatment stigma subscale had acceptable test-retest-reliability and good internal consistency. As hypothesised the subscale was significantly positively correlated with the SSRPH and the ISMI demonstrating convergent validity. The developmental process ensured content validity. Respondents gave the BACE a median rating of 8 on the 10-point quality scale. Readability scores indicated the measure can be understood by the average 11 to 12 year-old. The most highly endorsed barrier was ‘concern that it might harm my chances when applying for jobs’. The scale was finalised into a 30-item measure with a 12-item treatment stigma subscale. CONCLUSIONS: There is preliminary evidence demonstrating the reliability, validity and acceptability of the BACE. It can be used to ascertain key barriers to access to mental health care which may help to identify potential interventions to increase care seeking and service use. Further research is needed to establish its factor analytic structure and population norms.